Maternal gestational diabetes in singleton pregnancies conceived by ART may be modified by periconceptional B vitamins - Li, Minyu; Chen, Yanping; Wang, Yongxiang; Wang, Hong; Ding, Xueteng; Li, Guoju (Frontiers in Nutrition, 2023)
Background The risk of maternal gestational diabetes mellitus (GDM) may be influenced by pregnancies conceived through assisted reproductive technology (ART). However, the influence of the dosage of B vitamins (folate, vitamin B6 and vitamin B12) on GDM weren’t considered. Thus, we hypothesized that periconceptional B vitamins could modify maternal GDM in singleton pregnancies conceived by ART. Methods This study is a prospective cohort study using data from 3,252 women with singleton pregnancies and received a 75 g oral glucose tolerance test (OGTT) at 24–28 weeks of gestation. We included an interaction term in the multivariable logistic and linear regression models, respectively, to test our hypothesis. Results Women who underwent ART were significantly associated with the incidence of GDM compared with spontaneous pregnancy women. The adjusted odds ratio (aOR) was 1.59, and the 95% confidence interval (CI) was 1.08–2.34. ART pregnancies also elevated OGTT (oral glucose tolerance test) 1-h blood glucose levels and OGTT 2-h blood glucose levels (P < 0.05). A positive association between dietary vitamin B6 (aOR = 1.60, 95% CI: 1.13–2.27), dietary vitamin B12 (aOR = 1.88, 95% CI: 1.34–2.64) and dietary folate (aOR = 1.66, 95% CI: 1.19–2.32) with GDM risk comparing the highest to the lowest quartile (all Ptrend < 0.001). The aORs of GDM for inadequate (< 400 μg/day), adequate (400–800 μg/day), and excessive (> 800 μg/day) supplemental folate intake were 1.00, 0.93, and 1.30, respectively (Ptrend = 0.033). Since only the supplemental folate illustrates a statistically significant interaction with ART (P for interaction < 0.05), the association between ART and GDM and OGTT blood glucose levels stratifying by supplemental folate were further evaluated. These increased risks of GDM (aOR = 1.62, 95% CI: 1.39–3.39) and the regression coefficients (β) of 1-h blood glucose (β = 0.76, 95% CI: 0.39–1.13) and 2-h blood glucose (β = 0.60, 95% CI: 0.29–0.92) in the multiple linear regression model were significant only in the ART group with excessive supplemental folate (> 800 μg/day). Conclusion The risk of GDM is significantly elevated, particularly among those women who conceived ART with the intake of excessive supplemental folate (> 800 μg/day).